Association Analyses to Genetically Improve Drought and Freezing Tolerance of Faba Bean (Vicia faba L.). Issue 3 (1st May 2016) - Ali, Mohamed B.M.; Welna, Gregor C.; Sallam, Ahmed; Martsch, Regina; Balko, Christiane; Gebser, Björn; Sass, Olaf; Link, Wolfgang
Abstract : In parts of Central Europe, such as Germany, climate change will lead to increasing area utilization for winter types of faba bean ( Vicia faba L.) with improved tolerance to drought and freezing. Here, we present the first genome‐wide association analysis focusing on drought and freezing stress in a set of 189 German winter faba bean lines. We assessed proline, glycine betaine, soluble sugars, water content, membrane stability, and chlorophyll content in leaves of juvenile plants, with and without drought stress. To describe freezing tolerance under growth chamber conditions, we monitored the freezing symptoms of juvenile plants, such as loss of color and turgidity, freezing survival, and regrowth after freezing—achieving medium to high repeatabilities (0.43 < h 2 < 0.93). With 175 single‐nucleotide polymorphism (SNP) assays and 1147 amplified fragment length polymorphism (AFLP) assays, a total of 1322 (mostly mapped) DNA markers were utilized. We detected a total of 21 putative quantitative trait loci (QTL) for six of the traits, each explaining 6 to 15% of the phenotypic variance. Several phenotypically promising inbred lines were identified. The present results will greatly improve the prospects for including winter faba bean into German crop rotations in the near future.